Hospital mortality profile due to external causes in the State of Pernambuco: an epidemiological study (Research, Society and Development, 2021)
Objective: To describe and analyze hospital mortality from external causes in victims older than 1 year, in the state of Pernambuco, between 2015 and 2019. Methodology: Epidemiological study, descriptive of historical series, based on cases of deaths reported to the SIH / SUS of the the state of Pernambuco; with a 5-year cut-off (2015 to 2019). The following variables were analyzed: large group of causes, categories of causes, age group, sex and group of causes. Results: The number of deaths from 2015 to 2019 included 269,651 cases, 72.80% men and 27.20% women. The largest number of reported cases was observed in individuals between 20 and 29 years old, representing 18.25% of the total. Regarding the incidence of deaths between the sexes, there was a considerable increase in 2017, from 55.19 / 1000 to 59.43 / 1000 inhabitants. The most prevalent cause of death in all age groups was exposure to other specific factors, with a higher incidence affecting the age group between 20 and 59 years, representing 56.75% of all deaths in this age group. Conclusion: As pointed out above, there is a need to update the SIH, improving notifications in the private hospital care network, resulting in a more reliable number in the collected sample and also avoiding an increase in underreporting.